Evaluation of Knowledge and Practice of Pharmacy Professionals regarding the Risk of Medication Use during Pregnancy in Dessie Town, Northeast Ethiopia: A Cross-Sectional Study - Abdu Tuha; Yilak Gurbie; Haftom Gebregergs Hailu (Journal of Pregnancy)
Background. The developing organism is unique in its responsiveness to drugs and predictability of therapeutic effectiveness based on the adult which can lead to grave consequences in the neonate and child. Moreover, uncertainty about the risks of drug use in pregnancy could result in restrictive attitudes towards prescribing and dispensing medicines and their use. Pharmacists have huge duties to improve medication use, especially among pregnant women. The objective of this study is, hence, to assess the knowledge and practice of pharmacy professionals (PPs) towards the risk of medication use during pregnancy. Methodology. A questionnaire-based cross-sectional study was carried out over practicing community and hospital pharmacy professionals in Dessie town. They were asked about the safety of common drugs during pregnancy. It involves both prescription-only medications (POM) and over-the-counter (OTC) medications. Secondly, they were asked about their practice towards the risk of medication use during pregnancy. Both descriptive and analytical statistics were utilized. For descriptive analysis, results were expressed as numbers, percentages, and mean (± SD and 95% CI). Result. Seventy-six pharmacy professionals in Dessie, Northeast Ethiopia, took part in the study. Most of the respondents (64.5%) believed that amoxicillin is safe in all trimesters. 26 (34.2%) of participants knew that isotretinoin is unsafe for use by pregnant women. About dietary supplements, 32.9% of PPs reported that Vitamin A supplements are safe in all trimesters. There was a significant difference observed for study college and years of experience of the PPs in their score of knowledge test (p=0.020 and p=0.024, respectively). Additionally, there was a difference seen for gender (p=0.030), study college (p=0.036), and working institution (p=0.013) in their advice to pregnant women. Conclusion and Recommendation. Overall, PPs exhibited very low knowledge about drug safety during pregnancy. The absence of obligatory continuing pharmacy education for pharmacists is expected to have negatively affected the level of medication knowledge and consequently the pharmaceutical care services delivered in community and hospital pharmacies. As medication knowledge of PPs is poor, a multitude of strategies (educational, economic, managerial, and regulatory) should be designed by the government, universities, and pharmaceutical associations to improve the pharmacy professionals’ role in the healthcare system by providing them with continuous and up-to-date medication knowledge.